MENGHAYATI AJARAN HINDU KE DALAM DIRI - Sutarti, Titin (Widya Aksara, 2019)
Atman, which acts as the existence of life and the source of life for all beings, is the source of life in the life of this universe, human, animal and plant. In the teachings of Hinduism explained that "Brahman Atman Aikyam" which means that between Brahman (God) and Atman is single. Brahman is a source of atman and atman is part of Brahman. With the concept of Atman as part of the Brahman, it can be said that the nature of the two is the same, so that we can be of the view that God also resides in us as the highest existence in self, but he is not encased in our selfishness. When God is within, it means that he is very close to us so that we can more easily get closer to Him. In carrying out Hindu religious practices except carrying out ceremonial and ritual activities, but can be used with more simple things but requires commitment and sincerity and high awareness of the heart that is with Tapa, Bratha, Yoga, Samadhi, Bhakti. These five things if done thoroughly and in a single unit will bring someone to carry out activities as Hermit or Sanyasin Dormitory. But in the daily implementation, one can carry out partially and separately so that someone can continue to carry out their duties and obligations in the work environment and adjust to the patterns of life in the community. True happiness that arises from deep and deep awareness becomes the priority of the implementation of Tapa, Bratha, Yoga, Samadhi so that people can find and understand the God and Divinity in themselves.